Effect of incorporation of wheat bran, rice bran and banana peel powder on the mesostructure and physicochemical characteristics of biscuits - Ayoub, Wani Suhana; Zahoor, Insha; Dar, Aamir Hussain; Anjum, Nadira; Pandiselvam, R.; Farooq, Salma; Rusu, Alexandru Vasile; Rocha, João Miguel; Trif, Monica; Jeevarathinam, G. (Frontiers in Nutrition, 2022)
Various types of natural fiber-rich ingredients are added into bakery-based products to improve their fiber content for health promotional purposes. But the majority of these products usually include exotic dietary fiber components. The aim of this study was to develop biscuits incorporated with wheat bran, rice bran and banana peel powder and to evaluate the effects on physicochemical properties and sensory acceptability of these different biscuit samples. Wheat bran, rice bran and banana peel powder was used to substitute refined wheat flour in biscuit samples at different levels (0, 5, 10, 15, 20, 25, and 30%). The effect of wheat bran, rice bran and banana peel powder incorporation on proximate composition, physical characteristics, texture profile, color and sensory evaluation of biscuit samples were investigated. The moisture content of the product showed a significant (p ≤ 0.01) decreasing trend while as protein showed increasing trend with increasing level of incorporation of wheat bran, rice bran and banana peel powder. Also there was a considerable effect on L*(darkness to lightness), a*(greeness to redness), and b*(blueness to yellowness) values of biscuit samples. Among the physical parameters diameter and thickness decreased non-significantly (p ≤ 0.01) with the addition of different fibers whereas spread ratio and weight increases. Sensory attributes showed a significant (p ≤ 0.01) increasing trend with an increase in the level of incorporation of different fibers. Based on sensory evaluation biscuits prepared with 15% wheat bran, 15% rice bran, and 10% banana peel powder were rated best. The biscuits were packed in high density polyethylene (HDPE) boxes and were analyzed on different intervals viz. 0, 30, and 60th day. In samples of optimized biscuits, the ash content, protein, fat and color exhibited a non- significant tendency of declining over storage. It was discovered that the ash content dropped from0.86 to 0.67% in Wb4, 0.95 to 0.75% in Rb4, and 1.15to 0.92% in Bpp3. However there was a considerable increase in moisture content during storage.